Has Fintech Functioned as a Nudge for the SDGs Implementation? A Systematic Review - Hesan Zahid; Hammna Jillani (International Journal of Business and Economic Affairs, 2023)
An innovation in the financial industry, the merger of finance with technology known as Fin-Tech has triggered the paradigmb shift towards sustainability. This paper tries to investigate the link between fintech and the implementation of Sustainable Development Goals (SDGs) through a systematic review. During the era of the pandemic digital transfers and online platforms were mandatory requisites therefore, various articles on fintech and SDGs were identified based on inclusion criteria particularly published only during the wake of the COVID-19 period, which represents a novelty of this work. This research reveals the indispensable role of fintech in adopting various SDGs in several developed and developing economies thus, making way for new entrants in the field of technological innovations. The study recognizes that the revolution in the financial sector helps towards the attainment of SDGs while keeping the financial flows aligned and the environment intact henceforth, indicating the prime importance of adopting financial technologies for a sustainable society.